2019
DOI: 10.33899/ijvs.2019.125548.1068
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and In Vitro evaluation of a novel coated nanocomposite porous 3D scaffold for bone repair

Abstract: The aim of this study is to tissue engineer a 3D scaffold that can be used for load bearing segmental bone defects (SBDs) repair. Three different scaffolds were fabricated using cockle shell-derived CaCO 3 aragonite nanoparticles (CCAN), gelatin, dextran and dextrin with coated framework via Freeze-Drying Method (FDM) labeled as 5211, 5211 GTA+Alginate , 5211 PLA. Scaffolds were assessed using Scanning Electron Microscopy (SEM). The cytocompatibility of the organized scaffolds was assessed using cells multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…Other studies confirmed that the implant pores with a minimum diameter of 50 μm are required for bone ingrowth (27), this result came in line with the results of the present study, while other studies have shown better bone formation when pore size was 300-400 μm (28). The larger pores are favorable to vascularization, high oxygenation and subsequent bone formation (29,8). One important finding from the histopathological examination is regarding the quality of the regenerated tissues.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies confirmed that the implant pores with a minimum diameter of 50 μm are required for bone ingrowth (27), this result came in line with the results of the present study, while other studies have shown better bone formation when pore size was 300-400 μm (28). The larger pores are favorable to vascularization, high oxygenation and subsequent bone formation (29,8). One important finding from the histopathological examination is regarding the quality of the regenerated tissues.…”
Section: Resultssupporting
confidence: 91%
“…The CaCO3 of crab shell skeleton can change to (HA), Ca10(P04)6(OH)2, which is the main mineral of bone This articles an open access under the terms and conditions of the Creative Commons Attribution License (CC BY 4.0, https://creativecommons.org/licenses/by/4.0/). used to designing a suitable replacement biomaterial and considered as an ideal bone replacement (7,8). Formerly the HA had been used as a suitable replacement biomaterial in form of a scaffold for bone grafts in different surgical specialties due to its porous structures (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicated that the deproteinized lamb bone graft fulfilled almost all achievement properties for bone repairing. This finding agreed with Ibrahim et al (22) who used innovative scaffolds mixture from dextran, nanoparticles, gelatin, hydroxyapatite for bone reconstruction and restoration. However, in our study, bone graft played an essential role as a scaffold in bone tissue restoring near the standard furniture of defective bone and served as a bridge to improve the healing and achieve a perfect clinical outcome (23).…”
Section: Discussionsupporting
confidence: 92%
“…The chicken eggshells nano powder was liquefied in ninety nine percentage ethanol and sonicated for thirty mins. (1-3) droplets of suspension was loaded on top of the carbonenclosed copper grid and positioned on a filter paper to dehydrate at lab temperature previously observing by TEM 23,24 .…”
Section: Chicken Eggshells Description Electron Microscopy (Em)mentioning
confidence: 99%